From Cow to Climate—Tracing the Path of Dairy Sustainability: Unveiling the Impact on Sustainable Development Goals Through Bibliometric and Literature Analyses - Douglas Mwirigi; Mária Fekete-Farkas; Csaba Borbély (Animals)
Archeological evidence shows that dairy farming dates to the early Neolithic era in Europe, the Middle East, Asia, and Africa. Over time, it has evolved from domestication to intensive dairy farms with large, high-tech processing units. Dairy farming has contributed to economic growth, food production, employment, and processing industries. Nonetheless, it has been identified as a major contributor to climate change. This study explores the literature on dairy farming and sustainable development goals (SDGs) to identify current scholarly developments since the formulation and adoption of the SDGs in 2015 and themes for future research. This paper argues that sustainability shortfalls in dairy farming are primarily driven by human processes associated with commercialization and industrialization rather than the animals themselves, although biological emissions remain an inherent factor. Data were analyzed using R package, Excel, NVIVO, and VoS Viewer. A review of the literature showed that dairy farming and its contribution to sustainability has gained more scientific interest since 2015. Moreover, livestock management, feed production and management, stakeholder management, logistics and supply chain management, and waste management are the sources of environmental adversities associated with dairy farming. Notably, these are human processes developed from the commercialization of dairy farming and involve multiple stakeholders across the supply chain. While solutions are embedded within these processes, innovation emerges as a key driver of sustainability and a source of opportunities to strengthen sustainability in the dairy farming sector and achieve SDGs. Sustainability strategies, such as sustainable intensification, multifunctional agriculture, and agro-ecology should be implemented to improve sustainability in the dairy sector.